The Influence of Product Quality, Brand Image, and Brand Trust on Customer Loyalty of Honda Vario Motorcycle Products at The Honda Margo Mulyo Megah Dealership, South Jakarta - Muhammad Abiyyu Daffa Iqbal; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine Product Quality, Brand Image, and Brand Trust on Customer Loyalty for Honda Vario Motorcycle Products at the Honda Margo Mulyo Megah Dealer Pasar Minggu, South Jakarta. The technique uses Multiple Linear Regression Analysis and uses the SPSS program. The results of this study indicate that the partial regression coefficient of the Product Quality variable (X1) has no positive and significant effect on customer loyalty for Honda Vario motorcycle products based on the t-count value of 0.616 <1.984 t table and sig value 0.540> 0.05. The existence of a partial regression coefficient of the Brand Image variable (X2) has no positive and significant effect on Customer Loyalty for Honda Vario products based on the t-count value of 1.714 <1.984 and the sig value of 0.090> 0.05. And the partial regression coefficient of the Brand Trust variable (X3) has a positive and significant effect on customer loyalty for Honda Vario products based on the t-count value of 2.228>1.984 t table and sig value of 0.028 <0.05. Partially among the three variables whose results are significant is the Brand Trust Variable (X3) with a t-count value of 2.228>1.984 t table and a sig value of 0.028 <0.05. The results of this study expect that trust can increase Brand Trust (X3) which can support Customer Loyalty.